Non-Fermi-liquid behaviour close to the disappearance of ferromagnetism in CePd1-xRhx - Pikul, A.P.; Caroca-Canales, N.; Deppe, M.; Gegenwart, P.; Sereni, J.G.; Geibel, C.; Steglich, F.; Sereni, Julián (IOP Publishing, 2006)
Fil: Sereni, J.G. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina